Advances in the removal of diminutive colorectal polyps. (February 2014) - Paggi, Silvia; Radaelli, Franco; Repici, Alessandro; Hassan, Cesare
<x xml:space="preserve">Abstract</x> Diminutive polyps (<5 mm in diameter) represent the majority of polyps found during colonoscopy; about a half of them are adenomatous, with low risk of advanced neoplasia. Recent studies have demonstrated that cold polypectomy should be considered the recommended approach for resecting diminutive polyps and that cold snaring may be superior to cold forceps biopsy, at least for polyps of 4–5 mm. Recently, electronic chromoendoscopy has been applied to characterization of diminutive polyps to discriminate adenomatous from nonadenomatous lesions. Optical diagnosis of polyp histology could potentially exert huge cost savings by the 'resect and discard' strategy for diminutive polyps and 'leaving-in' for diminutive hyperplastic polyps in the recto-sigmoid colon. These policies represent the mainstay for adopting endoscopy-directed post-polypectomy surveillance strategies, endorsed by both American and European Endoscopy Societies. Accuracy of both histology and surveillance intervals predictions from academic centers have been encouraging, although the same performance has not been replicated in community practices.